(3GdfXQjI GdYGeI GdGFJeGfs - (3eMeO MSjf(B, (3efUhQs ((3GdGScfOGQjI(B:s (3OGQ GdLGeYjI GdLOjOI ddfTQ(B,s, 2001)
(3aj gPG GdcJGH (B: (3UhQ GdGFJeGf hVeGfI GdhSGFd GdJbdjOjI hGdMOjKI dMeGjJg GdcaGdI , GdQgf GdQSej f Mb GdGMJUGU , GdQgf GdMjGRj , Nbhb GdGeJjGRs
Keywords: (3GFJeGfs; (3GdcaGdIs